2019
DOI: 10.1002/hep.30899
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Progress Toward Elimination of Hepatitis B in Australia

Abstract: Background and Aims Chronic hepatitis B (CHB) is a significant global health concern, and the most prevalent blood‐borne virus in Australia. World Health Organization (WHO) member states have committed to global elimination, with targets to diagnose 90% of people living with CHB, treat 80% of those eligible, and reduce attributable deaths by 65% by the year 2030. Australia has committed to national targets of 80% diagnosed, 20% on treatment, and a 30% reduction in deaths by 2022. Approach and Results We constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 15 publications
0
58
0
Order By: Relevance
“…In 2017, an estimated 149 746 people living with chronic hepatitis B in Australia had been diagnosed, representing 68% of the total estimated population living with chronic hepatitis B and a modest increase from the 63% estimate in 2011. 307 The first National Hepatitis B Strategy 2010-13 308 sought to reduce disease transmission and the morbidity and mortality associated with hepatitis B. Furthermore, the introduction of highly effective HBV antiviral therapy in Australia with entecavir in 2005 and tenofovir in 2007 was accompanied by considerable increases in treatment uptake.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, an estimated 149 746 people living with chronic hepatitis B in Australia had been diagnosed, representing 68% of the total estimated population living with chronic hepatitis B and a modest increase from the 63% estimate in 2011. 307 The first National Hepatitis B Strategy 2010-13 308 sought to reduce disease transmission and the morbidity and mortality associated with hepatitis B. Furthermore, the introduction of highly effective HBV antiviral therapy in Australia with entecavir in 2005 and tenofovir in 2007 was accompanied by considerable increases in treatment uptake.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…Modeled trends between 2011 and 2017 show an ongoing modest increase (average 0·93% per year) in this proportion. 307 At the population-level, only a few people with chronic HBV infections (possibly 10-15%) would be recommended for treatment on the basis of national and international consensus guidelines. 309,310 These vaccination efforts are collectively reflected in the fact that Australia was recognised by WHO as meeting the regional control target of hepatitis B, which is a prevalence of less than 1% in children younger than 5 years.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…Previous modelling estimated that 215 264 to 237 894 people were living with CHB in Australia in 2016 . The model was initialized assuming 63.5% of people living with CHB were diagnosed (45.9% without care and 17.6% with care), sourced from modelled data which were estimated from Australian census data, hepatitis B surveillance system and national healthcare/medication subsidy programme (Table ). Health state distributions were assumed to be different for those in care and not in care.…”
Section: Methodsmentioning
confidence: 99%
“…Despite proportional increases in diagnoses, care engagement and treatment among people living with CHB since 2011, modelling data suggested that current diagnosis rates remain insufficient for Australia to reach the National Strategy or WHO Strategy targets. This suggests further scale‐up of testing, linkage to care and treatment is required, but such activities come at a cost.…”
Section: Introductionmentioning
confidence: 99%
“…Because hepatitis B immunoglobulin administration has been challenging in LMICs where MTCT is common, HBV diagnosis and treatment of eligible women of child-bearing age could also be used as a strategy to reduce MTCT 62 . Diagnosis and treatment of more HBV-infected individuals in general is required for HBV elimination [3][4][5] . An important goal for the next decade will be the discovery of agents that functionally cure rather than simply suppress HBV infection.…”
Section: MLmentioning
confidence: 99%